The Nature of Naked Singularity in Cosmology - Mohajan, Haradhan Kumar (Engineering International, 2017)
This paper discusses aspects of a naked singularity. If a star has exhausted its nuclear fuel, and it exceeds Chandrasekhar limit then it must undergo gravitational collapse and ultimately it forms black hole. A black hole is a space from where no massive particle or no signal comes to the external observer. As a result space-time singularity is formed; this must be hidden behind the black hole region which is called the cosmic censorship hypothesis, first proposed by Roger Penrose, which cloths the singularity to remain invisible to the external observers. It has not been possible, to obtain a proof despite many attempts to establish the validity of cosmic censorship and it remains an open problem. Hence, general relativity supports that naked singularity may be formed. A naked singularity implies that singularity is visible to an external observer. Sometimes it is not visible to the external observers, but it could be observable to the interior observers of the black hole region. This type of singularity is called local naked singularity.